ABUNDANT NOVEL SOLUTIONS OF THE CONFORMABLE LAKSHMANAN-PORSEZIAN-DANIEL MODEL - Ismael, Hajar Farhan; Baskonus, Haci Mehmet; Bulut, Hasan (Amer Inst Mathematical Sciences-Aims, 2021)
In this paper, three images of nonlinearity to the fractional Lakshmanan Porsezian Daniel model in birefringent fibers are investigated. The new bright, periodic wave and singular optical soliton solutions are constructed via the (m + G'/G) expansion method, which are applicable to the dynamics within the optical fibers. All solutions are novel compared with solutions obtained via different methods. All solutions verify the conformable Lakshmanan-Porsezian-Daniel model and also, for the existence the constraint conditions are utilized. Moreover, 2D and 3D for all solutions are plotted to more understand its physical characteristics.
Keywords: Fractional Lakshmanan-Porsezian-Daniel model; bright; periodic and singular solutions